The Comparison of Emotion Regulation Strategies in Adolescents with Oppositional Defiant Disorder and Normal - A. Ghasempour; V. Ramzani; A. Kalhori (Bihdād, 2014)
Introduction: Emotion regulation strategies were of affection factors in disruptive behavior disorders. The aim of the study was to comparison emotion regulation strategies in boy adolescents with oppositional defiant disorder and normal in Amol town. Materials and Methods: A causative- comparative design and the study statistical population was all boy student of Amol town high school. The study sample comprised 36 people (18 people with oppositional defiant and 18 people normal) who were selected by single- stage cluster sampling. Data was collected using Achenbach Youth Self-Report Scale (YSR) and Garnefski & Kraaij emotional regulation questionnaire. To analyze the data, multi-vitiate analyze of variance (MANOVA) was used. Results: The mean age of the adolescents with oppositional defiant disorder was 15/16±0/51and normal 15/11±0/67 years. The results of this study showed that adolescents with oppositional defiant disorder have negative emotion regulation strategies and adolescents normal have positive emotion regulation strategies. Conclusion: These findings highlighted the importance of positive and negative emotion regulation strategies in given oppositional defiant disorder in adolescents.